Availability and phytoremediation of zinc and copper in two Malaysian soils treated with sewage sludge - Binadam, Aishah Ramadan Mohamed (2017)
The disposal of municipal sewage sludge face serious challenges. Currently, over 3.2×106 metric tons of domestic sewage sludge in Malaysia are in need of safe disposal. Phytoremediation provides an efficient soil remediation solution since it uses plants to remove contaminants. A glasshouse experiment were conducted to assess the potential of four plant species (Jatropha curcas, Hibiscus cannabinus, Acacia mangium and Syzigium cumini) to the phytoremediation of excess Zn and Cu in Oxisol and in Ultisol amended by different rates of sewage sludge: 0, 5 and 10% v/v.